Effects of chess on cognitive functions and learning of schoolchildren: a systematic review (Research, Society and Development, 2020)
This study aimed to systematically review in the literature how the chess game influences cognition and the learning process in the school population. Method: Were consulted the PubMed, Scopus, SciELO and Lilacs digital databases, whose eligibility criteria selected randomized controlled trials and that the sample covered schoolchildren between 6:0 and 17:11 years, without cognitive, intellectual and/or learning impairment. The researches, selection and analysis of articles were carried out by two independent evaluators. Results: Five studies that relate chess set with cognitive performance and learning were found. The studies were showed that chess game benefits the cognition and learning of schoolchildren, but they differ as to the significance of this benefit.  Conclusions: There was a need for more studies on the theme and of high methodological quality, mainly related to students with learning difficulties.